Self-perceived impact of a community-based rehabilitation programme in Tanzania on quality of life of children with cerebral palsy and their carers - Van der Veen, Judith (Department of Health and Rehabilitation Sciences, 2015)
Includes bibliographical references (leaves 114-120).